A content analysis of RA 8584 and RA 10850 determining the rationale behind interior design regulation in the Philippines - Sanin, Nina Patricia S.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This qualitative study sought to examine RA 8534 and RA 10350 to determine the rationale behind the regulation of interior design in the Philippines. Utilizing the criteria used by Hardcastle (1977) on the factors that affect legal regulation of professions, the results from the content analysis reveal that interior design regulation in the Philippines have equal measures to protect both the public and protect the profession. In addition, RA 10350 has more potential to protect the public and develop the profession. Two key informants were interviewed to provide additional information on interior design regulation in the Philippines. The key informants have first-hand experience in designing the interior design regulation law and can provide insights as to the reasons such regulations are in place. Most of the answers from the interviews were directed towards, first, the establishment of the interior design profession in the Philippines and, then, addressing the global format of interior design practice to provide employment opportunities abroad. Results from the interviews suggest that the goals of interior design regulation are more focused on the protection and development of the profession. Furthermore, the changes made to the interior design law and their implications both lead to upgrading the standards of interior design practice to make Filipino interior designers globally recognized. It may be asserted that if the goal of the current interior design regulation law in the Philippines is to provide job opportunities, then entry requirements for interior designers can become a barrier to this goal. Legislators and institutions who regulate the interior design profession should be aware of other possible consequences to the requirements they impose on individuals. The rigorous requirements may limit entry to aspiring interior designers which can lead to the proliferation of illegal practitioners.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Interior decoration -- Philippines -- Law and legislation